A Critical evaluation of Ghazzalian and Kantian notions of mysticism and intuition: an Islamic Perspective (2005)
This research is an attempt to study the relationship between the Ghazzalian and Kantian thoughts on mysticism and intuition from an Islamic perspective. This study is intelligible when it is remembered that after Al-Ghazzali, mysticism in Islam was not the same again and even though. Kant was not a Mystic in the real sense of the word but his mystical notions appear similar to that of al-Ghazzali on many points especially on "mystical metaphysics. The study begins by tracing the concept and development of mysticism in Islam. It also enumerates some of the Muslim scholars who brought about reconciliation between mainstream Islam or orthodoxy and philosophical Sufism. One of whom and certainly the most famous and acknowledged in the West is al-lmam al Ghazzali. In addition, the study has traced the historical background of both the Ghazzalian and Kantian philosophical and metaphysical thoughts vis-it-vis mysticism and intuition. It also unravels both the post Kantian and Ghazzalian trends in mysticism and intuition. In doing, it has attempted to explain some metaphysical concepts germane to their thoughts on mysticism as popularly understood in the Ghazzalian and Kantian schools. It finally ends up revealing that today mysticism has become a euphemism for both laxity and licentiousness. Most mystics today hide behind their esoteric teachings to call for total or unwarranted liberalization of religious observances in the name of promoting religious understanding. As a result, there is perennial conflict in the philosophical mystical camps. The study therefore opines that it is the premonition of this problem that accounted for Kantian . skepticism and Ghazzalian demolition of philosophy.